THE ROLE OF PARENTS IN PROMOTING ACADEMIC SUCCESS - Kanta, Siddappa M (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Parents play a pivotal role in shaping their children’s academic success. Beyond providing basic needs, their engagement significantly impacts motivation, self-discipline, and academic performance. This paper examines the multifaceted roles parents undertake to support their children academically, emphasizing communication, involvement, and guidance. Parental involvement includes creating conducive learning environments at home, fostering open lines of communication with teachers, and encouraging positive attitudes toward education. Moreover, modeling behaviors such as consistent reading, problem-solving, and lifelong learning greatly influences children's perceptions of education. The paper also highlights challenges faced by parents in maintaining consistent involvement, including socioeconomic barriers and time constraints, and explores practical solutions to overcome them. Strategies such as participating in school activities, monitoring progress, and supporting emotional well-being are discussed, offering evidence-based insights. By actively collaborating with educators and understanding their children's unique needs, parents can foster a culture of learning and resilience. This research underscores the critical need for parental involvement in cultivating academic excellence, ultimately shaping the next generation's success.